2016
DOI: 10.1016/j.forsciint.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of point-of-care (POC) tests in screening elevated glucose and ketone body levels postmortem

Abstract: The aim was to evaluate the performance of point-of-care (POC) tests in detecting glucose and ketone bodies in postmortem (PM) samples and to assess the usefulness of POC tests in sample screening for more precise analyses. Glucose and ketone body, β-hydroxybutyrate (BHB), were measured from vitreous humor (VH) in 52 autopsy cases with a POC blood glucose monitoring device (BGMD). In addition glucose and ketone bodies, acetone (Ac) and acetoacetate (AcAc), were measured from urine samples in another set of 59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The test reduces pain in children and limits the need for nurses to collect blood intravenously. Walta et al [25] and Chong and Reineke [ 26 ] reported that when the blood ketone value is > 4 or 6 mmol/L, the detected value of the FreeStyle instrument will be lower than the actual value. Currently, all FreeStyle instruments used to detect blood ketones on the market are designed for diabetic patients, and lack speci c blood ketone assayers for KD patients.…”
Section: Discussionmentioning
confidence: 98%
“…The test reduces pain in children and limits the need for nurses to collect blood intravenously. Walta et al [25] and Chong and Reineke [ 26 ] reported that when the blood ketone value is > 4 or 6 mmol/L, the detected value of the FreeStyle instrument will be lower than the actual value. Currently, all FreeStyle instruments used to detect blood ketones on the market are designed for diabetic patients, and lack speci c blood ketone assayers for KD patients.…”
Section: Discussionmentioning
confidence: 98%
“…According to Cornelius Hess et al glucose concentration in vitreous fluid correlate with glycaemia previous to death ( Cornelius Hess, Musshoff, & Madea, 2011;. Moreover, estimation of HbA1c, fructosamine, or anhydroglucitol may provide useful data on the long-term glycemic control for individuals with diabetes (C. Hess et al, 2013;Lepik, Tõnisson, Kuudeberg, & Väli, 2018;Walta, Keltanen, Lindroos, & Sajantila, 2016). Though it has been thought that the glucose concentration in blood doesn't have high diagnostic validity because of its broad variation after death there are some studies that suggest post-mortal blood glucose analysis can be a useful diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid tests are used in public health-care settings such as nursing homes, physicians' offices, outpatient clinics, and in home healthcare where a physician or a nurse is able to run a quick test to decide if a patient should be diagnosed further in a hospital or whether the result is negative and a disease is excluded [4]. Checking of glucose and C-reactive protein levels are the most common tests run at outpatient sites and physicians' offices [5][6][7]. A small amount of blood lets physicians to take decision if a patient needs to be prescribed an antibiotic (CRP level) or his/her blood sugar level should be further diagnosed.…”
Section: Introductionmentioning
confidence: 99%